Analisis Faktor-Faktor Yang Mempengaruhi Waktu Tidak Produktif Idle Time Kapal Di Pelabuhan Tanjung Emas Semarang - Dedy Rusmiyanto; Ratna Hidayati (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2023)
Idle time or disturbing time is time wasted while the ship is moored is a classic problem that has not been solved in Indonesia. Tanjung Emas Port is the busiest port in Semarang City, Central Java, which is a stopover center for providers of sea transportation facilities and infrastructure in the context of loading and unloading means the transfer of cargo from and onto ships to be stockpiled into or directly transported to the place of the owner of the goods through the port dock using loading and unloading complementary equipment. This study aims to determine the effect of port services, ship engine tools, and loading and unloading productivity, on Idle Time at Tanjung Emas Port Semarang. The population in this study were ship crews from the deck departement division and the sample used in this study was 119 respondents. And do not use the sampling technique because the number of samples is the same as the population, then the data is analyzed using multiple liniar regression with the help of (software) Statistical Package (SPSS) Version 26. The formulation of the regression in this study is as follows: Y= 0,597 + 0,368X1 + 0,356X2 + 0,213X3 + m. From this equation it is know that the most dominant variable influencing Idle Time is the port Service variable with a regression coeffient of 0.368. The R2 test ( R The ) obtained a result of 0.443 or 44.3%, which means that Idle Time is influenced by the variable port Services, Loading and Unloadng Speed, and Ship Machinery Equipment which is equal to 44,3% and other factors that affect Idle Time Tanjung Emas Port Semarang, namely 100%.